Step-wise CAG@PLys@PDA-Cu2+ modification on micropatterned nanofibers for programmed endothelial healing - Bingcheng Yi; Boya Zhou; Zhenfeng Song; Lei Yu; Wenbo Wang; Wei Liu (Bioactive Materials, 2023)
Native-like endothelium regeneration is a prerequisite for material-guided small-diameter vascular regeneration. In this study, a novel strategy is proposed to achieve phase-adjusted endothelial healing by step-wise modification of parallel-microgroove-patterned (i.e., micropatterned) nanofibers with polydopamine-copper ion (PDA-Cu2+) complexes, polylysine (PLys) molecules, and Cys-Ala-Gly (CAG) peptides (CAG@PLys@PDA-Cu2+). Using electrospun poly(l-lactide-co-caprolactone) random nanofibers as the demonstrating biomaterial, step-wise modification of CAG@PLys@PDA-Cu2+ significantly enhanced substrate wettability and protein adsorption, exhibited an excellent antithrombotic surface and outstanding phase-adjusted capacity of endothelium regeneration involving cell adhesion, endothelial monolayer formation, and the regenerated endothelium maturation. Upon in vivo implantation for segmental replacement of rabbit carotid arteries, CAG@PLys@PDA-Cu2+ modified grafts (2 mm inner diameter) with micropatterns on inner surface effectively accelerated native-like endothelium regeneration within 1 week, with less platelet aggregates and inflammatory response compared to those on non-modified grafts. Prolonged observations at 6- and 12-weeks post-implantation demonstrated a positive vascular remodeling with almost fully covered endothelium and mature smooth muscle layer in the modified vascular grafts, accompanied with well-organized extracellular matrix. By contrast, non-modified vascular grafts induced a disorganized tissue formation with a high risk of thrombogenesis. In summary, step-wise modification of CAG@PLys@PDA-Cu2+ on micropatterned nanofibers can significantly promote endothelial healing without inflicting thrombosis, thus confirming a novel strategy for developing functional vascular grafts or other blood-contacting materials/devices.